Hot Spot : A Doctor's Diary From the Pandemic - Jahangir, Amir Alex, 1978- (Book collections on Project MUSE., 2022)
"A memoir of a Nashville trauma surgeon about the first year of the COVID-19 pandemic, drawing on his operation notes"--